Respuesta :

Answer:

option 4

Step-by-step explanation:

(f*g)(x) =(x² + x+ 1)*(x² - x -1)

           = x²*(x² - x -1)   + x(x² - x -1) + 1*( x² - x -1)

            = x²*x² - x²*x -x²*1   + x*x² - x*x -x*1 + x² - x -1

            = x⁴ - x³ - x² +x³ - x²  - x  + x² - x -1

           = x⁴  - x³ + x³  - x² - x² + x² - x - x - 1

       = x⁴ - x² - 2x - 1

Answer:

x^4 - x^2 - 2x - 1

Step-by-step explanation:

(x^2+x+1)(x^2-x-1) = x^4 - x^3 - x^2 + x^3 - x^2 - x + x^2 - x - 1

= x^4 - x^2 - 2x - 1